Syntagmatic And Paradigmatic Features Of Relative Syntagmas In Azerbaijani And English Languages - Hashim L. Akbarov (European Scientific Journal, ESJ, 2016)
The article deals with the definition of syntagma and relative syntagmas in Azerbaijani and English languages. At the same time, they are researched as syntactic units of linguistics. They are classified according to their types. Also, their meaning is spoken of widely in the article. It also talks about the semantic and stylistic features of syntagma as a unit of syntax. Syntagma is investigated as a syntactic unit of linguistics. Also, it comprehensively highlights its importance. This unit consisting of two members of the combined words is used in the functions of determining and being determined. It is explained as a semantic-syntactic event, and it studied and developed its semantic features. Signs perform the system of approaches in the form of syntagmatics and paradigmatics. Syntagmatic approaches are based on distributive potentials of signs. Their valence, but paradigmatic approaches are based on the selection of definite element of paradigm signs. Thus, this is the reason Saussure considers the morphology as the “sphere of paradigmatics”. The syntax is, however, known as the “sphere of syntagmatics”. A notion of “verticality” and “horizontality” exists even in the row of language signs of classic linguistics. Therefore, syntagmatics is explained as a “horizontality”, but paradigmatics as a “verticality”.